Hydrothermal Microwave: A New Route to Obtain Photoluminescent Crystalline BaTiO3 Nanoparticles - Moreira, M. L.; Mambrini, G. P.; Volanti, D. P. [UNESP]; Leite, E. R.; Orlandi, M. O. [UNESP]; Pizani, P. S.; Mastelaro, V. R.; Paiva-Santos, C. O. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Amer Chemical Soc, 2008)
Hydrothermal microwave method was used as a new route to synthesize pure BaTiO3 (BT) nanoparticles at 140 degrees C for 10 min under rapid reacting with stoichiometric Ba/Ti ratio. The crystalline products were characterized by X-ray powder diffraction (XRD) and the structure was refined by the Rietveld method from the tetragonal structure, which was supported by the Ti K-edge X-ray absorption near-edge structure (XANES). The pre-edge of Ti in the XANES spectra indicated that titanium ions are localized in a nonregular octahedron. Typical FT-Raman spectra for tetragonal BaTiO3 nanoparticles presented well-defined peaks, indicating a substantial short-range order in the system. However, a scattering peak at 810 cm was attributed to the presence of lattice OH groups, commonly found in materials obtained by hydrothermal process. Besides, the peak at 716 cm(-1) can be related to eventual Ba2+ defects in the BaTiO3 lattice. BaTiO3 (BT) nanoparticles presented spherical morphology with a non-uniform distribution of particle sizes. An intense and broad photoluminescence band was observed around the green color emission at room temperature. By means of an excitation energy of 2.54 eV (488 nm), it was noted that the maximum profile emission (2.2 eV) is smaller than the forbidden band gap energy of BaTiO3, indicating that certain localized levels within the band gap must exist.